Coexistência entre paisagens e ferrovia: fragmentos da linha São Borja, Itaqui, Barra do Quaraí - RS - Tondolo, Mayara Brasil (2023)
This research aims to record railway heritage from a landscape approach, with a systemic temporal analysis of the landscape where the deactivated railway line is located: São Borja, Itaqui, Barra do Quaraí – RS. For identification, characterization, registration and recognition of the railway heritage under study. From this perspective, sociocultural and biophysical dynamics are considered to construct a diagnosis of the location through the reading of landscape units (UPs) at the regional scale, and at the local scale the method of visual perception based on identification cards of the landscape elements around railway stations, with the purpose of creating a temporal record of the elements that compose it, especially the railway heritage, understanding the relationship between the railway and the surrounding landscape..